BYK-Gardner unveils spectro2go device for mobile colour and gloss measurement. Issue 12 (December 2020) - Unknown
Abstract : German-based instrument manufacturer BYK-Gardner is introducing the spectro2go, a new member of the spectro2guide product line, designed for measuring colour and gloss in a compact, handheld device. The new product joins the recently launched spectro2profiler instrument for analysing colour, gloss and 3D topography [ Additives for Polymers, September/October 2020, p9 ].